Review of Customer Satisfaction Index by INACA for Pattimura International Airport Ambon, Indonesia - Saraswati, Megananda; Rifai, Andri Irfan; Yudhistira, Pradana (DAS Institute, 2022)
The Customer Satisfaction Index (CSI) is one of the leading indicators in a service business. Customer satisfaction assessment in Indonesian Airports is carried out with a survey by the INACA team. The purpose of this analysis study is to know the reason ups and downs of customer satisfaction and also give suggestions to increase the score. This study uses data from INACA's survey. CSI of Pattimura Airport in the last five years (2017-2022) has been going through ups and downs. From 2018 to 2019, a Terminal Building Expansion and Beautification project impacted the existing facilities, resulting in reduced passenger comfort. However, the significant increase in CSI score in 2020 indicates that the project was successful. In 2021, the CSI of Pattimura Airport reached 4.63 with the interpretation that the passenger was very satisfied. The lowest score is 4.60, which is the aspect of shopping facilities, restaurants, and cafes, so it can be concluded that this aspect needs to be improved to increase customer satisfaction.